2016
DOI: 10.15406/ogij.2016.05.00184
|View full text |Cite
|
Sign up to set email alerts
|

Double Versus Single Dose Methotrexate Regimens in Management of Undisturbed Ectopic Pregnancy

Abstract: Objective: To assess the effectiveness and safety of double-dose methotrexate in comparing to single-dose methotrexate for management of ectopic pregnancy. Methods:A prospective randomized-controlled trial was conducted on 200 patients with ectopic pregnancy at the Obstetrics and gynecological Departments of Zagazig University, Egypt between June, 20 11 to May 2014. Patients were randomized into two groups, (group 1) who received a single dose 50 mg per meters squared surface area methotrexate (50 mg/m 2 IM on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(41 citation statements)
references
References 22 publications
1
39
1
Order By: Relevance
“…3). An analysis after exclusion of the study by Hamed et al27 showed similar results (RR 0.71, 95% CI 0.55-0.93; eight trials,18,19,24,25,28,[30][31][32] 777 patients, I 2 =7%).A subgroup analysis comparing the SDP with the multi-dose protocol revealed no significant difference in the adverse effect rate (RR 0.81, 95% CI 0.48-1.38; five trials,18,19,24,25,28 449 patients, I 2 =46%) (Fig. S3).…”
mentioning
confidence: 75%
See 4 more Smart Citations
“…3). An analysis after exclusion of the study by Hamed et al27 showed similar results (RR 0.71, 95% CI 0.55-0.93; eight trials,18,19,24,25,28,[30][31][32] 777 patients, I 2 =7%).A subgroup analysis comparing the SDP with the multi-dose protocol revealed no significant difference in the adverse effect rate (RR 0.81, 95% CI 0.48-1.38; five trials,18,19,24,25,28 449 patients, I 2 =46%) (Fig. S3).…”
mentioning
confidence: 75%
“…Although the precise reason for this result is unclear, the total methotrexate dose could have had a substantial influence. The time to resolution in the six studies included in the time analysis 18,19,25,27,31,32 ranged from 14 days to 41 days, regardless of the protocol used.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations